When should antihypertensive drug treatment be started? Discrepancies between the 2023 European Society of Hypertension and the 2024 European Society of Cardiology guidelines - Giuseppe Mancia; Guido Grassi; Sverre E. Kjeldsen (Italian Journal of Medicine)
One of the most important recommendations from the guidelines on hypertension is to decide when to lower blood pressure through antihypertensive treatment...